DIVERSITY OF Citrus spp. FROM PENAJAM PASER UTARA, EAST KALIMANTAN BASED ON MORPHOLOGICAL CHARACTERS - Linda Oktavianingsih; Noviana Crisdayanti; Muhammad Fauzi Arif; Medi Hendra (BIOTROPIA, 2024)
ARTICLE HIGLIGHTS- This research is the first study to provide data on the diversity of Citrus spp. from North Penajam Paser Regency (IKN) area, East Kalimantan for further development and breeding program. - This research offers new information on the distribution of Citrus spp. from the North Penajam Paser Regency (IKN) area, East Kalimantan. - This research provides information on the phenetic relationships among Citrus spp. from the North Penajam Paser Regency (IKN) area, East Kalimantan, and the morphological characteristics that play the most significant role in their clustering. ABSTRACTCitrus spp. is local Indonesian fruit with high diversity and widely distributed around Indonesia country. Diversity and relationship data of Citrus spp. from Penajam Paser Utara-East Kalimantan has never been studied before. This study aimed to provide the diversity and relationship data of Citrus spp. from Penajam Paser Utara using morphological characteristics which served as the basic data for further development and breeding. The research was conducted through observation and sampling, followed by characterization and scoring of morphological data, and lastly the data analysis. The research succeeded in finding 35 accessions of Citrus spp. consisting of C. limon “Jeruk Lemon”, C. suhuensis, “Jeruk Siam”, C. aurantiifolia “Jeruk Nipis”, C. sinensis “Jeruk Manis”, C. maxima “Jeruk Bali”, C. microcarpa “Jeruk Kalamansi”, and Citrus sp. "Jeruk Sunkist" spread in sub-district Penajam, Sepaku, Babulu, and Waru. The dendrogram to clustering Citrus spp. in PPU was divided into two large clusters. Cluster A was grouped based on the character of tree habitus, cordate leaf apex, entire leaf margin, pink mesocarp color, and seed absence. Cluster B was grouped based on the character of the shrubs habitus, acute and rounded leaf apex, crenate leaf margin, white to orange mesocarp color, and numerous seeds in the fruit. This diversity made Citrus spp. from Penajam Paser Utara had high potential value for further development through a plant breeding program.